Unraveling the spatial imprint of hominin and carnivore accumulations in early pleistocene african sites - Merino-Pelaz, Amanda (2024)
Reconstructions of palimpsest formation and dynamics in Early Pleistocene African archaeological deposits have undergone significant advances thanks to taphonomic research. However, the spatial imprint of different agents implicated in most of these accumulations still needs to be addressed. We hypothesize that different site formation dynamics may yield diverse spatial distributions of archaeological remains, reflecting the intervention of different agents (i.e., hominins, felids, hyaenids) in palimpsests. This study aims to investigate the spatial patterns of archaeological remains in a selected sample of Early Pleistocene accumulations with the goal of understanding and characterizing their spatial dynamics. Building on previous taphonomic interpretations of twelve paradigmatic archaeological deposits from Olduvai Bed I (FLK Zinj 22 A, PTK 22 A, DS 22B, FLK N 1-2 to 5, FLK NN 3, DK 1-3) and Koobi Fora (FxJj50, FxJj20 East and FxJj20 Main), we explore the spatial patterns of remains statistically and use hierarchical clustering on principal components analysis (HCPC) to group the highest-density spots at these sites based on a number of spatial variables. The results of this approach show that despite sharing a similar inhomogeneous pattern, anthropogenic sites and assemblages where carnivores played the main role display fundamentally different spatial features. Both types of spatial distributions also show statistical differences from modern hunter-gatherer campsites. Additional taphonomic particularities and differing formation processes of the analyzed accumulations also appear reflected in the classifications. This promising approach reveals crucial distinctions in spatial imprints related to site formation and agents' behavior, prompting further exploration of advanced spatial statistical techniques for characterizing archaeological intra-site patterns.